(untitled) (International Journal of Engineering and Computer Science, 2017)
This study aimed to ascertain whether the citizen interest significantly support the establishment of e-government in Nigeria. Kaduna Polytechnic was used as the case study. For a month, a cross-sectional survey was conducted in the institution having randomly selected departments from the stratified colleges of the institution. The data on agreement or disagreement from the respondents were used for assessments. The survey was carried out by the same questionnaire for all respondents. The total support or agreement to the establishment of e-government was 83.33% between the age of 25 to 68 years, with the rates of 50% and 33.33% in men and women, respectively; while the total disagreement to the establishment of e-government was 13.1% between this age range, with the rates of 6.67% and 6.43% in men and women, respectively (P<0.05). The agreed rates that are in support of e-government initiation were 22.62%, 21.43%, 28.57% and 10.71% between the ages of 25-35, 36-46, 47-57, 58-68, respectively. Disagreed rates were 3.57%, 2.39%, 3.09%, and 4.05%, for the same age ranges. While disagreed rates were 3.57%, 2.39%, 3.09%, and 4.05%, for the same age ranges. From our finding of the test performed, There are no significant difference between the interest of respondents with age range of 25 to 65, interest of male and female respondents and the interest of respondents with categories of computer knowledge for the establishment of e-government in Nigeria, since the ANOVA value of 0.163 is greater than significance level value of 0.05, chi-square value of 0.238 is greater than 0.05 and t value of 0.917 is greater than 0.05. There should be very serious awareness campaign and enlightenment before the establishment of egovernment since many respondents indicate zero knowledge of e-government.>